ROLE OF WOMEN IN STAND-UP COMEDY INDONESIA - Sihombing, Lambok Hermanto; Marcellian, Kevin; T, Okky Abrina; Piay, Yohanna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Stand-Up Comedy is a comedy genre where the person or the comedian presents material on their own stage, usually in front of a live audience, and using monologues on a topic. Stand-Up Comedy has developed with the times, nowadays not only men can play the role of comedians, but women can also make themselves into comedians and worthy. There are still many things that make female comedians treated differently or being underestimated. Female stand-up comedians are nowadays very popular among audiences or even those who want to become one. The purpose of this study is to provide an idea to the public that the profession of a female comedian is not detrimental to even some successful female comedians. Using the feminism and some cultural theories, this essay aims to find out the role of women in stand-up comedy industry and how they can freely speak up as a woman without being treated differently as men.